COMPUTER SIMULATION OF THERMOELASTICITY PROBLEMS FOR COMPLICATED SPATIAL PARTS - A. N. Chichko; Yu. V. Yatskevich; V. F. Sobolev; O. I. Chichko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
New approach for the simulation of stresses in 3-d parts of complicated configuration which are subjected to thermal treatment has been proposed in the paper. The paper gives computer calculations of distribution of normal stresses in time and space for «Hob» steel part.